Seleção de linhagens de feijão para produção e acúmulo de cálcio na planta - Domingues, Lucas da Silva (2013)
The common bean (Phaseolus vulgaris L.) is an important calcium source for human diet, thus the evaluation of the calcium use efficiency in common bean a relevant tool for crop sustainability. The aims of this study were to evaluate the response in common bean cultivars with different calcium concentrations in nutrient solution on dry matter production, yield components and calcium, potassium and magnesium accumulations; to investigate the association between these characters; to evaluate the genetic variability of lines for calcium availability in the solution; and identify lines of common bean-efficient and responsive to calcium application by different indexes. For this, three experiments were conducted from March 2011 to July 2012 in greenhouse, in a completely randomized design, in splitplots. In the first two experiments were tested calcium concentrations in nutrient solution from 1.10 to 4.95 mmol L-1 as components of the main plot and the BRS Expedito, Carioca and Iraí cultivars on subplots in the first experiment, with the exclusion of the cultivar Iraí in the second experiment. The third experiment evaluated the efficiency and the response of the calcium use of 12 different common bean lines at low (1.10 mmol L-1) and high (3.85 mmol L-1) calcium concentrations in the nutrient solution. Higher values for dry matter and grain yield components were observed for 3.30 mmol L-1 and 4.95 mmol L-1 calcium concentrations in the solution. The common bean cultivars acumulate greater quantity of calcium in the leaves, followed by stems, pods and grains. Highest accumulation of calcium in the leaves was obtained at a 4.95 mmol L-1 calcium concentration in the nutrient solution, and the calcium concentration in the leaves was 21 times higher than the value obtained in the bean grains. The increase of calcium concentration in the nutrient solution up to the concentration of 4.95 mmol L-1 does not change the absorption and the accumulation of potassium and magnesium in leaves and grains. Indirect selection by greater dry matter and higher values of the variables that form the grain yield in common bean will be efficient to increase the accumulation of calcium in grains. The lines L 15, L 234, L 246 and L 77 respond to the increase on calcium supply in the solution, because more calcium accumulates in grain in the cultivation with high calcium concentration. The lines L 246 and L 15 are calcium use efficient in the plant, in the acquisition and grain production, and are not responsive to calcium application. The line L 77 is calcium use efficient in the plant and in the grain production and is responsive to the calcium application in the nutrient solution.